Dealing with Students Pronunciation: the â€œSpelling Beeâ€ Effect - Khasanah, Uswatun; As Sabiq, Agus Husein (JET ADI BUANA, 2020)
Pronunciation is put on bottom list in English teaching-learning process, and students focused to learn grammar. The aim of this research was to investigate the effect of â€œSpelling Beeâ€ technique towards studentsâ€™ pronunciation. The researcher used the experimental method. The sample of the research was 63 students in seventh-grade MTs NU 01 Mambaul Hikmah Tegalwangi which was consist of 32 female students of seventh E as experimental class and 31 female students of seventh D as control class. The sampling technique used cluster random sampling. The instrument of the research used jumble letters and speaking test as pre-test and post-test which were analyzed using Microsoft Excel. The result of the research indicated that there was a significant difference between studentsâ€™ post-test in experimental class and control class. The mean score of the post-test in the experimental class was (71.806) while the score post-test in the control class was (23.306). Besides, the result of the t-test showed that t-stat (27.125) was higher than t-table (1.688) with a degree of freedom (df) = 36 as a result Ha was accepted and H0 was rejected. It meant that the â€œSpelling Beeâ€ technique had a significant influence in teaching pronunciation at seventh-grade of MTs NU 01 Mambaul Hikmah Tegalwangi. â€œSpelling Beeâ€ can be an alternative technique for teachers to improve studentsâ€™ pronunciation as well as their vocabulary and spelling skills.